Progress in full spectrum solar energy utilization by spectral beam splitting hybrid PV/T system. (May 2021) - Liang, Huaxu; Wang, Fuqiang; Yang, Luwei; Cheng, Ziming; Shuai, Yong; Tan, Heping
Abstract: Spectral beam splitting (SBS) hybrid PV/T system was a promising path for utilizing the full spectrum solar energy to cogenerate electricity and high-grade heat, with high conversion efficiency. To settle the balance between photoelectric and photothermal conversion performance for full spectrum solar energy utilization, the sunlight based on wavelength matching was divided into two or more parts at band-gap wavelength by a spectral beam splitter: sunlight with wavelength at and close to the band-gap of PV cell was directed to generate electricity, while the sunlight with rest wavelength was used for thermal output. SBS hybrid PV/T system can not only increase the overall efficiency, but can also decouple the photoelectric and photothermal conversion process in separated operation temperatures. The current state-of the-art review on the advancements of SBS hybrid PV/T system performed with the aid of nanofluids, nano-film and semitransparent PV cells was presented in this work, with emphasis on the latest developments during the last decade. Mechanisms of different SBS techniques, progress in system, thermodynamic and cost analyses of nanofluids, nano-film and semitransparent PV cell based SBS hybrid PV/T system were discussed in detail to give a comprehensive understanding of the nature of the full spectrum solar energy utilization and the factors impacting on the system efficiency. Though the cost increase can be offset by extra energy efficiency gain, the wavelength matching, optical losses and stability of SBS hybrid PV/T system needs to be solved for future industrial application. Highlights: Advancements of spectral beam splitting PV/T system was reviewed comprehensively. Mechanisms of spectral beam splitting techniques was reviewed comprehensively. Progress in system, thermodynamic and cost analyses were discussed in detail. Problems of system needs to be solved for future application were discussed.